‘For Mr Jentz going abroad’ : the educational journey of a teacher from Kremenets - Buczek, Katarzyna (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2021)
The article presents Karol Jentz, an early 19th-century physics teacher. Vilnius University sent him on an educational journey to Berlin, Vienna, Munich and Paris. During the journey, he visited numerous factories and expanded his knowledge. He was supposed to take the position of professor of technology at Vilnius University upon his return, but he unexpectedly died in Paris.
Keywords: technology; educational journey; Vilnius University; Karol Jentz